2020
DOI: 10.2196/19223
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized Health Monitoring System for Community-Dwelling Elderly People in Hong Kong: Design, Implementation, and Evaluation Study

Abstract: Background Telehealth is an effective means to assist existing health care systems, particularly for the current aging society. However, most extant telehealth systems employ individual data sources by offline data processing, which may not recognize health deterioration in a timely way. Objective Our study objective was two-fold: to design and implement an integrated, personalized telehealth system on a community-based level; and to evaluate the system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…Previous attempts have explored the application of data-driven assistive technologies in the field of cancer care [ 19 ], physiotherapy [ 20 ], cardiovascular disease [ 21 ], and elderly care at home [ 22 ]. Conversational agents [ 23 ] and data visualizations [ 19 ] are being developed for facilitating the interactions between the technologies and their users.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts have explored the application of data-driven assistive technologies in the field of cancer care [ 19 ], physiotherapy [ 20 ], cardiovascular disease [ 21 ], and elderly care at home [ 22 ]. Conversational agents [ 23 ] and data visualizations [ 19 ] are being developed for facilitating the interactions between the technologies and their users.…”
Section: Introductionmentioning
confidence: 99%
“…The older the elderly, the worse their performance [12,28,[44][45][46] Education level Populations with a high education level tend to use new technology [28,47] Region Compared to urban residents, rural ones are not likely to use new technology [48] E-health literacy E-health literacy is considered as a prerequisite of using mobile health app [5,15,30,47,49] Information literacy People skilled in computer and Internet use tend to adopt IHMT [13,14,38,46] Ethnicity and language Ethnic and linguistic differences affect users' acceptance and use behavior [13,44] Physical difficulties Physical difficulties are an obstacle for the elderly to accept new technologies [9] Self-efficacy People with high efficacy are more willing to accept new technology [11,13,16,30,39,45,[49][50][51] Compliance Procedures/equipment that can improve compliance are easy to be continuously used [19,24,29,[52][53][54][55] Skeptical attitudes Skepticism is a barrier to the elderly using new technology [12] Perceived demand Perceived demand is an essential factor in promoting the use of intelligent health management devices [8,21,56] 1. Objective factors…”
Section: Agementioning
confidence: 99%
“…These people are more inclined to adopt IHMT [38]. In Wang et al's study of the community-dwelling older adults in Hong Kong, it was found that the eHealth app for self-management is less likely to be used by older, unmarried, less educated, unemployed, and lower-income cancer survivors [56].…”
Section: Agementioning
confidence: 99%
“…Recent studies have provided increasing evidence that wrist temperature can be used for sleep monitoring [17,[20][21][22]. Low sleep quality and irregular sleep patterns become more prevalent with increasing age and dementia [23][24][25][26]. For example, poor nighttime sleep has been shown to be a key factor in older adults' tendency to have more daytime sleepiness [27], which has been associated with changes in circadian rhythms in older adults [28].…”
Section: Introductionmentioning
confidence: 99%